Nursing care for high-risk pregnant women (Research, Society and Development, 2023)
Objective: The present study aims to describe nurses' assistance on the main forms of prevention, diagnosis, and treatment of high-risk pregnancy. Methodology: The research is an integrative review of the literature, which consists of the construction of a comprehensive analysis of data from the literature, being used as an aid for discussions on research methods and results, in addition to containing numerous definitions of concepts, review of theories and evidence and analysis of methodological problems, causing a reflection on the carrying out of future studies. Results: The final sample resulted in 11 articles. Discussion: Therefore, it was observed how important it is to involve the conduct of prenatal care, in favor of detecting pathology through specific exams and how the nursing care process can positively assist in qualified and comprehensive assistance to pregnant women. Conclusion: Nurses act in a systematic way, with the aim of developing effective communication, offering the necessary information in a clear and understandable way. In which, care is essential for effective behavioral change. In this context, the importance of applying the self-care theory to the nursing process is concluded, facilitating the empowerment of pregnant women in their care, coping with anxiety, and reducing insecurity. The research will contribute to the development of novel studies, with the aim of promoting quality assistance to pregnant women and the birth of their child.